Redesain & Pengembangan Terminal Penumpang Pelabuhan Lasdap Siak Sri Indrapura Dengan Pendekatan Arsitektur Tropis - Muhammad Ikhsan; Wahyu Hidayat; Muhammad Rijal (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Siak Sri Indrapura LASDAP port is the main gateway to the Siak city through water transport. However, the condition of the passenger terminal facilities at the Port of Siak Sri Indrapura LASDAP is still not sufficient, because the absence of the terminal arrivals and departures for domestic and international passenger ship that do not have a clear circulation between the arrival and departure of passengers aboard, the presence of the passenger terminal at the LASDAP Port of Siak Sri Indrapura is currently an area of 3,150 m² is no longer adequate to accommodate the activities of domestic and international visits coming to the Siak city. It is necessary to redesign and development. Development is done by adding land located next to the LASDAP Port of Siak Sri Indrapura, so that the total area of land to be designed is an area of 1.5 ha were adjusted by considering the capacity of the space required. The port is one of the nodes in the transport network. The passenger terminal is a meeting place of two transport systems are equipped with service facilities and processing of passengers and luggages, as well as the administration. Redesign & Development Port Passenger Terminal LASDAP Siak Sri Indrapura will apply the concept of